High-performance depth map coding for 3D-AVC. Issue 6 (September 2016) - Kang, Jinmi; Chung, Kidong
Abstract Achieving high-performance coding for a depth map is one of the most important challenges in 3D video coding. In this paper, a quality enhancement method is proposed to accomplish better coding efficiency. A new technique separating contour and flat regions is designed, and a contour-aware quality enhancement algorithm is presented to improve depth map quality. We also propose a fast mode decision process to reduce computational complexity. The proposed fast algorithm uses similarity between texture video and depth map coding. The encoding process for a depth map is terminated early by using coded information from a texture video. Experimental results show that the quality of the depth map is improved by 0.11–0.59 dB, which translates into a bit rate saving of 2.19–8.19 %. The proposed fast algorithm saves encoding time, on average, by 36.4 %.